MODEL USAHATANI OPTIMAL PADA LAHAN KERING BERIRIGASI AIR TANAH DI KABUPATEN LOMBOK TIMUR - Halimatus Sadiyah (AGROTEKSOS, Jurnal Ilmiah Ilmu Pertanian, 2023)
To overcome the problem of scarcity of water resources, the NTB Regional Government has built several groundwater irrigation services in East Lombok Regency. Given that the development of surface water irrigation schemes requires a lot of investment, the facilities built by the government must be used massively for the prosperity of the people. In general, the purpose of this study is to build a farming model that can provide the best income for farmers. In particular, the objectives of this study are to: 1) Examine the management system of groundwater irrigation schemes in meeting water needs for farmers. 2) Analyze changes in planting patterns, planting intensity and income of farmers who receive groundwater irrigation scheme services. 3) Build a farming model that can provide maximum income for farmers using groundwater irrigation schemes. 4) Analyze the factors that influence farmers in determining planting patterns. This research will be conducted in East Lombok District on the grounds that East Lombok District has the highest number of groundwater irrigation service schemes. Respondents of groundwater irrigation/pump management were determined by proportional random sampling in 3 villages with the most groundwater irrigation networks. Taking into consideration the distance and field terrain as well as the number of irrigation networks in the 3 villages, 6 management respondents were determined in North Pringgabaya Village, 4 in Labuan Lombok Village and 5 in Gunung Malang Village, so that all respondents managing this groundwater irrigation network amounted to 15 people (groundwater irrigation network). Farmer respondents were then selected based on respondents who managed the selected groundwater irrigation network. From the survey, it was determined that 5 (five) dominant commodities cultivated by farmers were corn, tobacco from the people, chilies, tomatoes and shallots. The number of farmers was set at 30 respondents on each type of crop cultivated, except for tomato plants only found 22 respondents. All respondents amounted to 142 farmers with a distribution of 69 people from North Pringgabaya Village, 40 people from Gunung Malang Village and 33 people from Labuan Lombok Village. The business model is built using a Linear Mathematical Model where the ABQM program is used to solve the solution. The results showed that the infrastructure for providing groundwater/pump irrigation networks was built by the government (subsidies) and management was handed over to the community. Its officers are elected by deliberation. Operational costs are borne by the community at a rate of Rp 35,000-Rp 60,000 per service hour depending on the amount of well water discharge. The provision of groundwater irrigation networks has changed the planting pattern of farmers, from planting once a year in the rainy season only with field rice or corn, to 2 or three plantings, commodities cultivated in addition to corn junga horticultural commodities such as one tomato chili and shallots, and plantation commodities, namely tobacco. The optimization results show that the planting pattern of onions and corn provides the highest income for farmers with a large income reaching Rp. 27,136,137.44. Farm income, land area, capital owned by farmers and the number of workers in the family are factors that determine farmers in choosing planting patterns to be applied.